The Effect of Capital, Training, and Motivation on Micro, Small and Medium Enterprises in Malang - Alfaizi, Muhammad Riza; Azizah, Rias Dyatmika; Almira, Chelsie Aurelia; Pradana, Ayub Wijayati Sapta (East Asian Journal of Multidisciplinary Research, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia's economy, especially in regions like Malang City. This study explores the influence of capital, training, and motivation provided by BAZNAS Microfinance on MSME development. Utilizing a quantitative research approach, the findings indicate that access to low-interest loans significantly enhances production capacity and operational management. Additionally, training programs improve technical skills and digital marketing capabilities, fostering collaboration and competitive advantage among MSMEs. Furthermore, motivational support encourages entrepreneurial resilience and long-term growth. The research concludes that the integration of capital, training, and motivation is crucial for the sustainable development of MSMEs. Recommendations include enhancing training quality, streamlining capital access, and offering personalized motivational support to entrepreneurs.